The Effect of Exercise Therapy on Muscular Strength, Bone Mineral Density and Quality of Life in Postmenopausal Women With Osteoporosis: A Systematic Review - Narges Jahantigh Akbari; Hoda Niknam; Sedigheh Sadat Naimi; Nahid Tahan; Bijan Danesh Shahreki; Ali Jahantigh Akbari; Yousef Nooshiravani; Negar Asad-Sajjadi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Osteoporosis is a widespread skeletal condition due to decreased muscle strength and bone density. The most common complications are fractures followed by pain and reduced quality of life (QoL). Therefore, this research aimed to examine the effect of exercise therapy on muscle strength, QoL, and bone mass in osteoporotic women. Materials & Methods Available literature was reviewed using ScienceDirect, PubMed, Google Scholar, and Cochrane. Studies were considered eligible if they were randomized controlled trials (RCT) conducted on postmenopausal osteoporotic women, used exercise therapy as an intervention, and investigated muscle strength, QoL, and bone mass as outcomes. Two authors independently assessed the quality of the articles using the physiotherapy evidence database (PEDro) scale. The Cohen's d effect size was computed by dividing the mean standardized difference by the standard deviation to measure the treatment effect, which includes exercise therapy. Results Seven papers were chosen to be included in this research. Their PEDro scores varied between 6 and 9 out of a possible 10. The effect size mean differences, resulting from exercise therapy, ranged from 0.32 to 0.63, indicating "small" to "moderate" effects in enhancing the condition of osteoporotic postmenopausal women. It was reported that there was a small effect size in 5 studies and a medium effect size in 2 studies. The research findings suggested the effect of balance, strengthening, stretching, stability, and motor control exercises on bone mass and muscle strength in osteoporotic postmenopausal women. Conclusion Findings indicate that exercise therapy interventions positively affect muscular strength, QoL, and bone mass in osteoporotic postmenopausal women. Additional well-conducted research is required to support this assumption further.